Persistent depletion of plasma gelsolin (pGSN) after exposure of mice to heavy silicon ions - Kanokporn Noy Rithidech (2018)
© 2018 Little is known about plasma proteins that can be used as biomarkers for early and late responses to radiation. The purpose of this study was to determine a link between depletion of plasma gelsolin (pGSN) and cell-death as well as inflammatory responses in the lung (one of the tissues known to be radiosensitive) of the same exposed CBA/CaJ mice after exposure to heavy silicon (28Si) ions. To prevent the development of multiple organ dysfunctions, pGSN (an important component of the extracellular actin-scavenging system) is responsible for the removal of actin that is released into the circulation during inflammation and from dying cells. We evaluated the levels of pGSN in plasma collected from groups of mice (5 mice in each) at 1 week (wk) and 1 month (1 mo) after exposure whole body to different doses of28Si ions, i.e. 0, 0.1, 0.25, or 0.5 Gy (2 fractionated exposures, 15 days apart that totaled each selected dose). In the same mouse, the measurements of pGSN levels were coupled with the quantitation of injuries in the lung, determined by (a) the levels of cleaved poly (ADP-ribose) polymerase (cleaved-PARP), a marker of apoptotic cell-death, (b) the levels of activated nuclear factor-kappa B (NF-κB) and selected cytokines, i.e. tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), and IL-6, from tissue-lysates of the lung. Further, the ratio of neutrophils and lymphocytes (N/L) was determined in the same mouse. Our data indicated: (i) the magnitude of pGSN depletion was dependent to radiation dose at both harvest times, (ii) a persistent depletion of pGSN up to 1 mo post-exposure to 0.25 or 0.5 Gy of28Si ions, (iii) an inverse-correlation between pGSN depletion and increased levels of cleaved-PARP, including activated NF-κB/pro-inflammatory cytokines in the lung, and (iv) at both harvest times, statistically significant increases in the N/L ratio in groups of mice exposed to 0.5 Gy only. Our findings suggested that depletion in pGSN levels reflects not only the responses to28Si-ion exposure at both harvest times but also early and late-occurring damage.